Therapeutic dimensions of play therapy relationship - Landreth, Garry; Play Therapy Institute (Denton, TX : Play Therapy Institute, 2003)
Lecture on making contact with children through play therapy. Covers essential dimensions in facilitating play therapy relations, four healing messages, necessary conditions for helping children grow, and helping children to discover their own resources
Title from title screen
Psychologist: Dr. Garry Landreth
DVD Format
Keywords: Play therapy; Play; Child psychology